2015
DOI: 10.1089/thy.2014.0561
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Association Between Thyroid Cancer and Breast Cancer

Abstract: The overall risk of second primary TC or BC is increased in patients with prior BC or TC, respectively. The early detection of second cancer might have contributed to these findings. However, BC that coexisted with TC had a higher expression of hormone receptors, suggesting an association between the molecular pathogenesis of TC and BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 25 publications
9
64
0
1
Order By: Relevance
“…These results are in agreement with previous studies showing that TC in patients with BC was diagnosed at an earlier stage than ordinary TC and is specific for papillary TC . Similarly, An et al reported that after excluding incidentally detected cases by imaging modalities during follow‐up of BC, the SIR for secondary TC decreased from 2.18 to 1.73 in a Korean cohort.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement with previous studies showing that TC in patients with BC was diagnosed at an earlier stage than ordinary TC and is specific for papillary TC . Similarly, An et al reported that after excluding incidentally detected cases by imaging modalities during follow‐up of BC, the SIR for secondary TC decreased from 2.18 to 1.73 in a Korean cohort.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of TC was 1.8% in 13 978 patients with BC, and the SIR of secondary TC for female patients with BC was as high as 4.48 (95% CI, 3.95‐5.44) compared with Chinese females in the general population and was 2.52 (95% CI, 2.22‐3.06) compared with areas of high urbanization. These results are comparable with those of previous studies, which showed an SIR ranging from 1.16 to 4.75 in patients with BC . More active surveillance of BC could lead to more incidental diagnoses of TC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The latter ones include genetic susceptibility, as is the case for Cowden and Cowden-like syndromes (89), as well as a common molecular mechanism mediated by sex steroid receptors. In this regard, compared to control groups of breast cancer as the only malignancy, the expression of both ER and progesterone receptor (PR) was found to be significantly increased in breast cancer specimens from women who also had DTC, regardless of which of the two cancers had occurred first and/or of the latency to detection of the second malignancy (90, 91). Interestingly, evidence has been provided showing that rearranged during transfection/papillary thyroid carcinoma (RET/PTC) oncogene is induced by estrogen in breast cancer cells, and the RET/PTC kinase signaling enhances estrogen-driven cell proliferation (92, 93).…”
Section: Resultsmentioning
confidence: 99%
“…The SIR value was calculated according to the estimated incidence of BC (37.86/100,000) and TC (10.32/ 100,000) in China in 2011 [11]. The SIR value of TC was higher compared with the value obtained in previous studies (from 1.2 to 4.6) [1215]. The increased incidence of TC followed by the occurrence of BC might be attributed to the incidental detection of TC during follow-up of BC or to the frequent health check-ups following BC.…”
Section: Discussionmentioning
confidence: 99%